Comparing performance of bastion host on cloud using Amazon web services vs terraform - Sahana Bailuguttu; Akshatha S. Chavan; Oorja Pal; Kavya Sannakavalappa; Dipto Chakrabarti (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
In addition to security advantages like implementing defense in depth and complying with compliance standards, current bastion services are simple to deploy and fit into the DevOps culture. Bastions continue to be the most dependable and secure options for secure access to cloud infrastructures because they offer administrative simplicity without surrendering compliance and security. In this paper, an experimental set up was conducted to measure the cycle time it takes to provision resources using manual point-and-click graphical user interface (GUI) in Amazon web services (AWS) and time it takes for codified infrastructure to make application programming interface (API) calls using terraform. It also focuses on the design and deployment of Bastion host on AWS and terraform, and the comparison between the two with respect to various parameters.